REVEGETATION IN SOLAR PHOTOVOLTAIC FARMS IN MEDITERRANEAN AREAS - Perez-de-los-Reyes, Caridad; Sanchez Ormeno, Monica; Amoros Ortiz-Villajos, Jose Angel; Garcia Navarro, F. Jesus; Campos Gallego, Juan; Martinez Lopez, Raquel; Rubio Berenguer, Francisca; la Rubia Carretero, Oscar (FRESENIUS ENVIRONMENTAL BULLETIN, 2013)
In order to ascertain the native species best adapted to different soil and climatic conditions in Mediterranean areas degraded by the installation of solar photovoltaic farms, six shrub species, which would act as a hedge, were planted around the perimeter of a photovoltaic farm (Olea europaea var. sylvestris, Pistacia lentiscus, Pistacia terebinthus, Quercus coccifera, Quercus ilex and Retama sphaerocarpa). In the midst of the solar panels, eight species for revegetation, acting as a cover to protect the soil, were also planted (Cistus ladanifer, Cistus monspeliensis, Lavandula angustifolia, Lavandula stoechas, Phillyrea angustifolia, Rosmarinus officinalis, Romarinus officinalis var. postratus and Thymus vulgaris) under conditions of sun or shade (shaded by solar panels). During 2009 and 2010 the plants of each species were checked and their survival and growth were recorded. In the hedge, Retama sphaerocarpa (100%), Olea europaea var. sylvestris (95.8%) and Pistacia lentiscus (95.8%) had the highest survival percentages. These were also the species that presented the highest apical growth after two years (18.3 +/- 14.7, 12.3 +/- 12.4 and 12.1 +/- 5.1 cm, respectively). Only two of the species planted under the solar panels had a survival percentage above 50% and these were Cistus monspeliensis (62.5%) and Phillyrea angustifolia (97.9%), with increases of the apical growth by 25.6 +/- 9.9 cm and 10.3 +/- 9.8 cm, respectively. The development of plants under either sun or shade was not a statistically significant factor. The results can be extrapolated to other Mediterranean areas dealing with the same problems.
The following values have no corresponding Zotero field: pub-location: ANGERSTR. 12, 85354 FREISING, GERMANY publisher: PARLAR SCIENTIFIC PUBLICATIONS (P S P)
Keywords: apical growth; Mediterranean shrubs; species factor; sun-shade conditions; Survival

REVEGETATION IN SOLAR PHOTOVOLTAIC FARMS IN MEDITERRANEAN AREAS - Perez-de-los-Reyes, Caridad; Sanchez Ormeno, Monica; Amoros Ortiz-Villajos, Jose Angel; Garcia Navarro, F Jesus; Campos Gallego, Juan; Martinez Lopez, Raquel; Rubio Berenguer, Francisca; la Rubia Carretero, Oscar (FRESENIUS ENVIRONMENTAL BULLETIN, 2013)
In order to ascertain the native species best adapted to different soil and climatic conditions in Mediterranean areas degraded by the installation of solar photovoltaic farms, six shrub species, which would act as a hedge, were planted around the perimeter of a photovoltaic farm (Olea europaea var. sylvestris, Pistacia lentiscus, Pistacia terebinthus, Quercus coccifera, Quercus ilex and Retama sphaerocarpa). In the midst of the solar panels, eight species for revegetation, acting as a cover to protect the soil, were also planted (Cistus ladanifer, Cistus monspeliensis, Lavandula angustifolia, Lavandula stoechas, Phillyrea angustifolia, Rosmarinus officinalis, Romarinus officinalis var. postratus and Thymus vulgaris) under conditions of sun or shade (shaded by solar panels). During 2009 and 2010 the plants of each species were checked and their survival and growth were recorded. In the hedge, Retama sphaerocarpa (100%), Olea europaea var. sylvestris (95.8%) and Pistacia lentiscus (95.8%) had the highest survival percentages. These were also the species that presented the highest apical growth after two years (18.3 +/- 14.7, 12.3 +/- 12.4 and 12.1 +/- 5.1 cm, respectively). Only two of the species planted under the solar panels had a survival percentage above 50% and these were Cistus monspeliensis (62.5%) and Phillyrea angustifolia (97.9%), with increases of the apical growth by 25.6 +/- 9.9 cm and 10.3 +/- 9.8 cm, respectively. The development of plants under either sun or shade was not a statistically significant factor. The results can be extrapolated to other Mediterranean areas dealing with the same problems.
Keywords: apical growth; Mediterranean shrubs; species factor; sun-shade conditions; Survival

Evidence for plant traits driving specific drought resistance. A community field experiment - Matías, Luis; Quero, José Luis; Zamora, Regino; Castro, Jorge (Environmental and Experimental Botany, 2012)
Drought is known to be a major bottleneck for woody-community recruitment. The species-speciﬁc resistance to drought and factors involved in its variation are of special interest to forecast community fate. We performed an experiment under natural ﬁeld conditions from winter 2006 to end summer 2008 to investigate the structural responses of woody saplings to nine combinations of light (three habitats differing in plant cover:forest, shrubland, and open) andwater (three climate scenarios: drier, current and wetter summers). Our working hypothesis is that plant strategies to cope with drought are determined by habitat characteristics and/or variation of plant traits, and that these different strategies may determine community composition and dynamics. Eight woody species with different life forms and successional stages (trees, mid-successional shrubs, and pioneer shrubs) were selected for the comparison, including therefore species representative of the entire woody community. We explored drought resistance at the population level (DS), the relations of the different morphological traits to DS, and the potential importance for plants of inter-speciﬁc trade-offs. DS ranged from 0% to 99% for the different species, depending on the habitat. Some structural traits were found to be related to DS: positively with total biomass and leaf mass ratio (LMR) and negatively with leaf area-root mass ratio (LARMR). Contrary to previous studies, the present work revealed no evidence of trade-offs, such as survival in forest vs. growth in open, or growth in forest vs. growth in open. Accordingly, some species with low DS values (Acer opalus and Pinus sylvestris) would be threatened under the future climate conditions, while species having structural characteristics to increase their resistance under expected dry years in coming decades (i.e., high LMR and total biomass or low LARMR, such as Quercus ilex and the shrub Cytisus scoparius) might enhance their recruitment probabilities. Thus, species-speciﬁc plant traits, and their effect on DS, may ﬁlter future community assemblages.
Keywords: biomass allocation; climate change; Mediterranean; Structural traits; Survival; Trade-off

Forest microhabitats differentially influence seedling phenology of two co-existing Mediterranean oak species - Monnier, Yogan; Prévosto, Bernard; Ripert, Christian; Corbani, Aude C.; Fernandez, Catherine (Journal of Vegetation Science, 2012)
Question How do forest microhabitats impact seasonal microclimate conditions and phenological seedling strategies in two co-occurring Mediterranean Quercus species with different leaf habits? Location Pinus halepensis woodlands, Provence, SE France. Methods Ninety sets of three acorns of Quercus ilex (evergreen) or Quercus pubescens (winter-deciduous) were sown under various P. halepensis canopy cover conditions. Canopy cover and litter depth were measured at each sowing point, and soil moisture and temperature were measured twice monthly. Seedling phenology and aerial development were monitored during the second growing season under different microhabitats. Results During rainy periods, soil moisture was higher under open canopy and thinner litter layers, whereas during summer drought soil moisture was higher under dense canopy and thicker litter layers. Quercus pubescens seedlings had higher growth activity than Q. ilex before summer drought, whereas the pattern reversed during autumnal growth. Dense canopy cover strongly delayed budburst and decreased foliar development in Q. pubescens, which was more affected than Q. ilex. Depending on species phenology, litter thickness can influence height growth of flushes during early summer. Conclusions Quercus pubescens has a phenological strategy to allow development of maximal foliar area before summer drought, a typical growth strategy of Mediterranean winter-deciduous species. In contrast, later phenological activity of evergreen Q. ilex enables it to cope with the dry period and capitalize on autumnal precipitation events. Dense cover acts as shelter in the dry season but can reduce soil moisture during wetter seasons. In contrast to Q. ilex, Q. pubescens appeared strongly dependent on canopy cover, suggesting that Q. ilex has a larger regeneration niche in Aleppo pine woodlands. In the context of global change, this ‘microhabitat effect’ on species-specific phenological strategy underlines the need to consider effects of local environmental conditions on regenerating species.
Keywords: Canopy; litter; Phenology; Quercus ilex; Quercus pubescens; Soil moisture; Survival

Why do large, nitrogen rich seedlings better resist stressful transplanting conditions? A physiological analysis in two functionally contrasting Mediterranean forest species - Cuesta, Bárbara; Villar-Salvador, Pedro; Puértolas, Jaime; Jacobs, Douglass F.; Rey Benayas, José M. (Forest Ecology and Management, 2010)
We analysed the physiological bases that explain why large and high nitrogen (N) concentration seedlings frequently have improved survival and growth relative to small seedlings in Mediterranean woodland plantations. Large seedlings of Aleppo pine (Pinus halepensisMill.) and holm oak (Quercus ilex L.) with high N concentration (L+), and small seedlings with either high (S+) or low (S−) N concentration, were planted on two sites of different weed competition intensity that created contrasting stress conditions. Seedling survival, growth, gas exchange, N remobilization (NR) and uptake (NU), and water potential were assessed through the ﬁrst growing season. Weeds reduced survival and growth, but seedling response to weed competition varied among phenotypes and between species. At the end of the ﬁrst growing season, L+ Aleppo pine seedlings had higher survival than both small seedling types in presence of weeds but no differences were observed in absence of weeds. Mortality differences among phenotypes occurred in spring but not in summer. L+ Aleppo pines grew more than small Aleppo pines independently of weed competition. No holm oak seedling type survived in presence of weeds and no mortality differences among phenotypes where observed in absence of weeds, although L+ holm oak seedlings grew more than small seedlings. Mortality and growth differences in Aleppo pine were linked to marked physiological differences among phenotypes while physiological differences were small among holm oak phenotypes. L+ Aleppo pines had greater root growth, gas exchange, NR, and NU than small seedlings, irrespective of their N concentration. Seedling size in Aleppo pine had a greater role in the performance of transplanted seedlings than N concentration. The functional differences among oak phenotypes were small whereas they were large in pine seedlings, which led to smaller differences in transplanting performance in holm oak than in pine. This suggests that the nursery seedling quality improvement for planting in dry sites could depend on the species-speciﬁc phenotypic plasticity and functional strategy. Improved transplanting performance in large Aleppo pine seedlings relative to small seedlings was linked to greater gas exchange, root growth and N cycling.
Keywords: competition; Nitrogen remobilization; photosynthesis; Pinus halepensis; Quercus ilex; Root growth; Stomatal conductance; Survival; water potential

No effect of habitat fragmentation on post-fledging, first-year and adult survival in the middle spotted woodpecker - Robles, Hugo; Ciudad, Carlos; Vera, Rubén; Baglione, Vittorio (Ecography, 2007)
Despite its relevance for the dynamics of populations, the ecological mechanisms underlying juvenile and adult survival are poorly known in most bird species. This study focuses on the effect of habitat fragmentation on early post-fledging, first-year and adult survival of the middle spotted woodpecker Dendrocopus medius by combining data of radio-tagged and ringed birds. Among juveniles, most deaths occurred during the first three weeks after fledging (survival rate: 0.35990.077) and were mainly caused by predation. After independence, birds faced another critical period during their first autumn-winter that lowered first-year survival further (0.25590.044), whereas adult mortality was considerably lower (annual survival rate: 0.78690.074). We did not find any significant effect of habitat fragmentation (measured as patch size and connectivity) on juvenile or adult survival. Sex ratio at fledging did not differ significantly from parity (proportion of females: 0.513) and was not correlated to patch size. Regardless of age, survival did not differ between the sexes, suggesting that a femalebiased mortality was not the mechanism behind the presence of unpaired territorial males in this population. Lighter nestlings underwent significantly higher post-fledging mortality, indicating that conditions in the nest may substantially affect survival later in life.
Keywords: Habitat fragmentation; middle spotted woodpecker; Mortality (voyant); Survival

No effect of habitat fragmentation on post-fledging, first-year and adult survival in the middle spotted woodpecker - Robles, Hugo; Ciudad, Carlos; Vera, Rubén; Baglione, Vittorio (Ecography, 2007)
Despite its relevance for the dynamics of populations, the ecological mechanisms underlying juvenile and adult survival are poorly known in most bird species. This study focuses on the effect of habitat fragmentation on early post-fledging, first-year and adult survival of the middle spotted woodpecker Dendrocopus medius by combining data of radio-tagged and ringed birds. Among juveniles, most deaths occurred during the first three weeks after fledging (survival rate: 0.35990.077) and were mainly caused by predation. After independence, birds faced another critical period during their first autumn-winter that lowered first-year survival further (0.25590.044), whereas adult mortality was considerably lower (annual survival rate: 0.78690.074). We did not find any significant effect of habitat fragmentation (measured as patch size and connectivity) on juvenile or adult survival. Sex ratio at fledging did not differ significantly from parity (proportion of females: 0.513) and was not correlated to patch size. Regardless of age, survival did not differ between the sexes, suggesting that a femalebiased mortality was not the mechanism behind the presence of unpaired territorial males in this population. Lighter nestlings underwent significantly higher post-fledging mortality, indicating that conditions in the nest may substantially affect survival later in life.
Keywords: Habitat fragmentation; middle spotted woodpecker; Mortality (voyant); Survival

The role of disturbance in the co-existence of the evergreen Quercus ilex and the deciduous Quercus cerrioides - Bonfil, Consuelo; Cortés, Pilar; Espelta, Josep Maria; Retana, Javier (Journal of Vegetation Science, 2004)
Question: Which is the response of the evergreen Quercus ilex and the deciduous Q. cerrioides to repeated disturbances? Location: central Catalonia (northeastern Spain), in the areas affected by two of the largest historically recorded wildfires in NE Spain: the Bages-Berguedà fire (24 300 ha forested area burned in July 1994), and the Solsonès fire (14 300 ha burned in 1998). Methods: Survival and growth of individuals of Quercus ilex and Q. cerrioides were evaluated in plants subjected to different fire histories and experimental disturbances (burning, cutting or clipping) applied either before or after summer. Results: Survival was high (> 99%), with both species showing a similar high resistance to disturbances. Growth after experimental disturbance was positively related to the size of the individual before the latest forest fire occurred. Fire history had a large effect on resprout growth, as the repeated incidence of disturbances lowered the capacity of individuals to grow. The type and season of experimental disturbance experienced by plants had a large effect. Individuals that experienced total above-ground loss had lower growth rates than those with partial loss. A similar pattern was observed in individuals disturbed after the summer in relation to those disturbed before summer. Conclusions: The larger growth rates recorded in Q. cerrioides across all fire histories and experimental treatments, and the higher vulnerability of Q. ilex to increased fire frequency, intensity of experimental disturbance, and disturbance season, provide evidence for the relatively high susceptibility of the latter to repeated disturbances. This view disagrees with the larger resilience of this species compared to co-existing deciduous oaks, as reported.
Keywords: Burning; clipping; fire; Growth; Mediterranean Region; Quercus; resilience; resprouting; Survival

The role of disturbance in the co-existence of the evergreen Quercus ilex and the deciduous Quercus cerrioides - Bonfil, Consuelo; Cortés, Pilar; Espelta, Josep Maria; Retana, Javier (Journal of Vegetation Science, 2004)
Question: Which is the response of the evergreen Quercus ilex and the deciduous Q. cerrioides to repeated disturbances? Location: central Catalonia (northeastern Spain), in the areas affected by two of the largest historically recorded wildfires in NE Spain: the Bages-Berguedà fire (24 300 ha forested area burned in July 1994), and the Solsonès fire (14 300 ha burned in 1998). Methods: Survival and growth of individuals of Quercus ilex and Q. cerrioides were evaluated in plants subjected to different fire histories and experimental disturbances (burning, cutting or clipping) applied either before or after summer. Results: Survival was high (> 99%), with both species showing a similar high resistance to disturbances. Growth after experimental disturbance was positively related to the size of the individual before the latest forest fire occurred. Fire history had a large effect on resprout growth, as the repeated incidence of disturbances lowered the capacity of individuals to grow. The type and season of experimental disturbance experienced by plants had a large effect. Individuals that experienced total above-ground loss had lower growth rates than those with partial loss. A similar pattern was observed in individuals disturbed after the summer in relation to those disturbed before summer. Conclusions: The larger growth rates recorded in Q. cerrioides across all fire histories and experimental treatments, and the higher vulnerability of Q. ilex to increased fire frequency, intensity of experimental disturbance, and disturbance season, provide evidence for the relatively high susceptibility of the latter to repeated disturbances. This view disagrees with the larger resilience of this species compared to co-existing deciduous oaks, as reported.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Burning; clipping; fire; Growth; Mediterranean Region; Quercus; resilience; resprouting; Survival

Growth and survival in Quercus ilex L. seedlings after irrigation and artificial shading on Mediterranean set-aside agricultural land - Rey Benayas, José M (Ann. For. Sci., 1998)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and survival of 800 Quercus ilex sp. ballota seedlings in set-aside agricultural land under semi-arid Mediterranean climate conditions in central Spain. The survival and growth of the seedlings were monitored for 3 years after planting with an experimental design that included all four combinations of: i) irrigation or no irrigation during the dry season; and ii) artificial shading or no shading. Significant differences in survival and growth (height, stem diameter and crown projected area) were found among treatments. Survival was lowest (53 %) in the control plots, and very similar (around 93 %) for the irrigation, shade and combined treatments. Most of the mortality occurred after the first dry season. The high survival rate in irrigated but not shaded plots coincided with a thick layer of the weed Amaranthus retroflexus L. (in the first dry season). Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth and crown projected area in interaction with shade. Growth measurements were correlated to microclimatic conditions in the plots as measured by the amounts of water and actual evapotranspiration. We conclude that the attenuation of summer stress must be considered in the early stages of successful plantation practice of set-aside agricultural land in a dry environment.
Keywords: Agricultural land; Growth; irrigation; shade; Survival

Growth and survival in Quercus ilex L. seedlings after irrigation and artificial shading on Mediterranean set-aside agricultural land - Rey Benayas, José M. (Ann. For. Sci., 1998)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and survival of 800 Quercus ilex sp. ballota seedlings in set-aside agricultural land under semi-arid Mediterranean climate conditions in central Spain. The survival and growth of the seedlings were monitored for 3 years after planting with an experimental design that included all four combinations of: i) irrigation or no irrigation during the dry season; and ii) artificial shading or no shading. Significant differences in survival and growth (height, stem diameter and crown projected area) were found among treatments. Survival was lowest (53 %) in the control plots, and very similar (around 93 %) for the irrigation, shade and combined treatments. Most of the mortality occurred after the first dry season. The high survival rate in irrigated but not shaded plots coincided with a thick layer of the weed Amaranthus retroflexus L. (in the first dry season). Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth and crown projected area in interaction with shade. Growth measurements were correlated to microclimatic conditions in the plots as measured by the amounts of water and actual evapotranspiration. We conclude that the attenuation of summer stress must be considered in the early stages of successful plantation practice of set-aside agricultural land in a dry environment.
Keywords: Agricultural land; Growth; irrigation; shade; Survival

Mortalidad y crecimiento de plantones de quercus ilex en una tierra agrícola abandonada en toledo - Rey Benayas, Jose Maria (II Congreso Forestal Español, 1997)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and mortality of 800 Quercus ilex' subsp. ball()ta seedlings in a set-aside agricultural land under semi-arid Mediterranean climate conditions in Toledo, Spain. The mortality and growth of the seedlings were monitored for three years after planting with an experimental design that included all four combinations of i) irrigation or no irrigation in the dry season and ii) artificial shading or no shading. Significant differences in mortality and growth (height, stem diameter and crown projected area) were found among treatments. Mortality was highest (47%) in the control plots, and very similar (around 7%) for the irrigation, shade, and combined treatments. Most of the mortality occurred after the first dry season. The low mortality in irrigated but not shaded plots in the first dry season is attributed to the protective role of a thick layer of the weed Amaranthus retroflexus L. Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth, and crown projected area in interaction with shade. We conclude that the reduction of summer stress must be considered in the early stages for successfull afforestation practices with oaks in set-aside agricultural lands of dry environments.
Keywords: Agriculturalland; Growth; irrigation; shade; Survival